英語作為外語的國小畢業生詞彙量、詞彙閾值與閱讀理解 Vocabulary Size, Lexical Threshold, and Reading Comprehension of Elementary-School EFL Learners - 胡翠君 Tsui-Chun Hu; 許媖茹 Ying-Ju Hsu; 宋曜廷 Yao-Ting Sung (National Taiwan Normal University, 2020)
本研究檢視臺灣國小畢業生英語詞彙量與閱讀理解之間的相關性，依此推估臺灣國小畢業生欲展現該學習年段閱讀理解程度所需要達到的詞彙閾值（lexical threshold），並探究臺灣國小畢業生英語詞彙量的分布狀況，以提供具體證據來評估當前國小英語詞彙學習目標（應用300個字詞）是否合理。本研究運用英語能力診斷及認證系統（Diagnosis and Certification of English Competency, DCEC），對1,903名國小畢業生進行詞彙和閱讀兩子測驗施測。本研究有三重貢獻：第一為瞭解臺灣小學生畢業時的詞彙量分布概況；其二為闡明設定詞彙量、詞彙閾值對於設計理想英語文課綱與課程的重要性；其三為彌補英語文課綱詞彙量設定時未採用實徵證據之不足。倡議詞彙量之設定，應從語言技能運用的觀點，先提出各階段所欲達成的語言技能層次，再探討獲致該語言技能層次所需的詞彙閾值（最小詞彙量），最後以該詞彙閾值作為課綱詞彙量設定之參考。 In this study, we examined the relationship between the vocabulary size and reading comprehension of Taiwanese elementary-school graduates. We identified a lexical threshold that they need to cross to demonstrate adequate reading comprehension. We investigated the English vocabulary sizes of Taiwanese elementary-school graduates to provide solid evidence of whether the current English vocabulary-learning goal (300 words) is reasonable. We employed the Diagnosis and Certification of English Competency (DCEC) as the main assessment tool and administered the DCEC-Vocabulary Size (DCEC-VS) and DCEC-Reading Comprehension (DCEC-RC) subtests to 1903 elementary-school graduates. This study has three crucial contributions. The first contribution is evidence that explains the distribution of the vocabulary sizes of Taiwanese elementary-school graduates. The second contribution is proof of how crucial vocabulary size and lexical threshold are for an ideal curriculum. The third contribution compensates for a lack of empirical evidence regarding a lexical threshold at the elementary-school level. We propose that the application of language skills should be the main consideration when setting a lexical threshold. The degree to which specific language skills should be acquired at each level should first be proposed, followed by an exploration of the lexical threshold (minimum vocabulary size) required to match goals for specific language skills at each level. Finally, the lexical threshold proposed should be used as reference when determining the vocabulary size in the curriculum.